Global and regional problems towards an interdisciplinary study - Aalto, Pami 1972-; Harle, Vilho; Moisio, Sami (International political economy of new regionalisms series, 2011)
This book addresses global and regional interactions and the complex policy problems that often characterise this agenda. Such enhanced communication is crucial for improving the capacity of IR to engage with concrete issues that today are of high policy relevance for international organisations, states, diplomats, mediators and humankind in general